Suriname. Significant Achievements 2023 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2024)
The report on significant achievements in Suriname in 2023 highlights the collaboration between the Government and various international organizations, such as the United Nations Development Program (UNDP), the Inter-American Institute for Cooperation on Agriculture (IICA) and the Inter-American Bank Development (IDB). Among the notable achievements are the construction and operation of plant nurseries in districts such as Coronie and the Upper Suriname River Basin, aimed at training farmers in fruit crop propagation techniques. The implementation of protected agriculture structures with hydroponic systems in districts such as Nickerie, in order to increase the production of leafy green vegetables. The installation of solar dryers and a fish processing unit to improve the efficiency and quality of local products. Strengthening farmers' knowledge in areas such as the cultivation of dragon fruit and the use of climate-smart technologies, as well as the installation of microfertigation systems. Support for agricultural entrepreneurs to improve their processing facilities and facilitate their access to formal marketing channels. The installation of micro-irrigation systems on demonstration plots to improve water use efficiency and increase productivity at Nickerie. The training of officials, teachers and students in water resources management. The initiative to establish large-scale agroforestry plots in Maroon communities, with the aim of promoting sustainable agricultural practices and increasing household incomes. The identification of challenges faced by rural women to design technical solutions that improve their resilience to climate change. And direct technical support to government departments in agricultural competitiveness and sustainable productivity programs.